2021
DOI: 10.1523/jneurosci.0410-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Glutamate/GABA Cotransmission Modulates Hippocampal Circuits and Supports Long-Term Potentiation

Abstract: Subcortical input engages in cortico-hippocampal information processing. Neurons of the hypothalamic supramammillary nucleus (SuM) innervate the dentate gyrus (DG) by coreleasing two contrasting fast neurotransmitters, glutamate and GABA and thereby support spatial navigation and contextual memory. However, the synaptic mechanisms by which SuM neurons regulate the DG activity and synaptic plasticity are not well understood. The DG comprises excitatory granule cells (GCs) as well as inhibitory interneurons (INs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 94 publications
(136 reference statements)
1
14
0
Order By: Relevance
“…This more targeted form of inhibition ( 66 ) than the typical disynaptic feedforward inhibition, which could be spatially isolated from excitatory inputs, may exclude the possibility that the action of GABAergic cotransmission of SuM inputs is depolarizing ( 60 , 63 ). However, it should be noted that SuM neurons also excite dentate INs, driving feedforward inhibition to GCs ( 14 , 15 ). Therefore, we cannot exclude the possibility that GABAergic inputs derived from feedforward inhibition recruited by SuM inputs contribute to regulation of GC firing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This more targeted form of inhibition ( 66 ) than the typical disynaptic feedforward inhibition, which could be spatially isolated from excitatory inputs, may exclude the possibility that the action of GABAergic cotransmission of SuM inputs is depolarizing ( 60 , 63 ). However, it should be noted that SuM neurons also excite dentate INs, driving feedforward inhibition to GCs ( 14 , 15 ). Therefore, we cannot exclude the possibility that GABAergic inputs derived from feedforward inhibition recruited by SuM inputs contribute to regulation of GC firing.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that the SuM neurons make monosynaptic connections to granule cells (GCs), the DG principal neurons, and corelease glutamate and GABA onto GCs ( 10 , 12 15 ). This glutamatergic and GABAergic cotransmission exerts a net excitatory effect on GCs and modulates GC firing through temporal association with entorhinal cortical inputs ( 14 , 15 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We chose these two specific intervals to investigate the effects of excitatory postsynaptic conductance (EPSG) and inhibitory postsynaptic conductance (IPSG) selectively on action potential generation. The fast‐spiking phenotype of hippocampal INs or putative soma‐targeting INs recorded at room temperature (21–24°C) were defined by their maximal firing rate >65 Hz and coefficient of variation <0.2 in response to a 1 s depolarizing current injection (Ajibola et al., 2021; Lien & Jonas, 2003). Recordings were made with Multiclamp 700B amplifiers (Molecular Devices), low‐pass filtered at 4 kHz and digitized at 10 kHz (Digidata 1440A, Molecular Devices), and controlled by pCLAMP 10.3 software (Molecular Devices).…”
Section: Methodsmentioning
confidence: 99%
“…GluA2/3‐, PV‐, or SST‐immunoreactive cells were identified in z‐ stack images and examined for colocalization with ChR2‐eYFP‐expressing cells. The co‐labelled cells were counted using the counter plugin in Fiji (a distribution of ImageJ software, NIH, Bethesda, MD, USA, 1.53c; Ajibola et al., 2021; Schindelin et al., 2012).…”
Section: Methodsmentioning
confidence: 99%